2014
DOI: 10.1002/eji.201444823
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral regulatory T cells restrain microglia/macrophage‐mediated inflammatory responses via IL‐10

Abstract: Forkhead box P3 (Foxp3)+ regulatory T (Treg) cells maintain the immune tolerance and prevent inflammatory responses in the periphery. However, the presence of Treg cells in the central nervous system under steady state has not been studied. Here, for the first time, we show a substantial TCRαβ+CD4+Foxp3+ T-cell population (cerebral Treg cells) in the normal rat cerebrum, constituting more than 15% of the cerebral CD4+ T-cell compartment. Cerebral Treg cells showed an activated/memory phenotype and expressed ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
129
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(132 citation statements)
references
References 46 publications
2
129
0
1
Order By: Relevance
“…In agreement with our results, Tregs modulated the function of macrophages through IL-4, IL-10, and IL-13, but not TGF-b. 34,35 Furthermore, previous reports have indicated that PI3K/Akt signaling is responsible for macrophage polarization, and GSK3b/ PTEN lies up-stream of PI3K/Akt. 37,45 Our results also indicate that Tregs can reverse the hemoglobininduced reduction in GSK3b in microglia and subsequently reverse the decrease in P-PTEN.…”
Section: Foxp3mentioning
confidence: 99%
“…In agreement with our results, Tregs modulated the function of macrophages through IL-4, IL-10, and IL-13, but not TGF-b. 34,35 Furthermore, previous reports have indicated that PI3K/Akt signaling is responsible for macrophage polarization, and GSK3b/ PTEN lies up-stream of PI3K/Akt. 37,45 Our results also indicate that Tregs can reverse the hemoglobininduced reduction in GSK3b in microglia and subsequently reverse the decrease in P-PTEN.…”
Section: Foxp3mentioning
confidence: 99%
“…In rats, T reg phenotypes have been less studied; we have observed that approximately 20% of CD4 T regs was observed [80].…”
Section: Cd25mentioning
confidence: 98%
“…In the rat cerebrum, a substantial of Treg cells with activated/memory phenotype (TCRab + CD4 + Foxp3 + CD44H + CD62L À Treg cells) are identified, and these Treg cells also express higher levels of other activation/memory markers including ICOS, CD103, KLRG1 and CTLA-4 [66]. Studies in cerebrospinal fluid of human support the idea that T cells in the CNS are mainly activated/memory phenotype [67].…”
Section: Novel Treg Cells In the Central Nervous System (Cns)mentioning
confidence: 86%
“…Studies in cerebrospinal fluid of human support the idea that T cells in the CNS are mainly activated/memory phenotype [67]. Cerebral Treg cells in rats constitute more than 15% of the cerebral CD4 + T cell compartment [66]. Notably, brain astrocytes may have a regulatory role in the control of cerebral Treg cells, because brain astrocytes contribute to Foxp3 expression in Treg cells through IL-2/STAT5 signaling [66].…”
Section: Novel Treg Cells In the Central Nervous System (Cns)mentioning
confidence: 94%